2022
DOI: 10.12737/szf-82202212
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic pulsations in 1–4 mHz frequency range (Pc5/Pi3) in the magnetotail at different levels of disturbances in the interplanetary medium

Abstract: In this paper, we study parameters of geomagnetic pulsations in the 1–4 mHz frequency range (Pc5/Pi3) in the magnetotail, utilizing data obtained by Cluster satellites at different levels of fluctuations in the interplanetary magnetic field (IMF) and the solar wind dynamic pressure in 2016. Particular attention is given to the conditions of “zero” disturbance when amplitudes of fluctuations in the interplanetary medium are smaller compared to their typical values. Both under quiet and disturbed conditions, wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…An example of pulsations in the tail observed at a low amplitude of IMF fluctuations on July 18, 2016 (day 200) is given in Figure 2. This finding is similar to that described in [Nosikova et al, 2022] for the August 8, 2007 event when largescale pulsations in the magnetotail also occurred against the background of almost complete switch-off of external disturbances. To understand whether such a coincidence is accidental or not, we analyze the distributions of Pc5/Pi3 pulsation parameters in the magnetotail at different fluctuation amplitudes in front of the bowshock.…”
Section: Event 2: July 18 2016supporting
confidence: 89%
See 2 more Smart Citations
“…An example of pulsations in the tail observed at a low amplitude of IMF fluctuations on July 18, 2016 (day 200) is given in Figure 2. This finding is similar to that described in [Nosikova et al, 2022] for the August 8, 2007 event when largescale pulsations in the magnetotail also occurred against the background of almost complete switch-off of external disturbances. To understand whether such a coincidence is accidental or not, we analyze the distributions of Pc5/Pi3 pulsation parameters in the magnetotail at different fluctuation amplitudes in front of the bowshock.…”
Section: Event 2: July 18 2016supporting
confidence: 89%
“…Changes in the pulsation parameters are observed 2-4 hrs before the substorm without an obvious external trigger. Nosikova et al [2022] for one case have shown a high coherence of pulsations in both polar caps and large-scale pulsations in the magnetotail observable at the "zero" level of external disturbance. The question about the statistical relationship of non-triggered substorms and other transient processes in the magnetosphere with the parameters of geomagnetic pulsations in the range of a few millihertz in the magnetotail calls for a separate study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation